Resource Utilization and Repetitive Construction Scheduling using the Discrete Event Simulation Method - Fadjar, Adnan; Akbar Ali, Amar; Setiawan, Arief (Engineering, Technology & Applied Science Research, 2025)
The efficient utilization of resources in repetitive construction projects is crucial to optimizing schedules and reducing costs. This study investigates the application of Discrete Event Simulation (DES) to enhance resource utilization in scheduling repetitive construction activities, specifically the construction of Type-36 houses in Palu City, Indonesia. Traditional project-based planning methods, such as the Critical Path Method (CPM), are compared with production-based planning approaches. The study shows that although CPM can effectively determine project completion times, it falls short in optimizing resource allocation, particularly in scenarios involving repetitive tasks. By employing the DES tool SIMUL8, the study models the construction process and simulates various resource allocation scenarios to identify the optimal resources required. The results indicate that DES provides a more dynamic and accurate analysis, allowing real-time adjustments and improved resource management. The study concludes that integrating DES into construction project management can significantly enhance efficiency, reduce project duration, and optimize resource utilization.